1972
DOI: 10.1128/iai.6.4.459-464.1972
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Stable Hemolysins of Group A Streptococci VIII. Leukotoxic and Antiphagocytic Effects of Streptolysins S and O

Abstract: Streptolysin S exists in a cell-bound form and as an extracellular complex between a nonspecific carrier (serum, serum albumin, ribonucleic acid [RNA], Triton, Tween) and a hemolytic moiety (probably a peptide) synthesized by streptococci. Although all the forms of streptolysin S, at 100 hemolytic units, killed mouse leukocyte monolayers, the time needed to kill 100% of the cells varied with the different streptolysin S preparations. Whereas 30 min was sufficient for the cell-bound hemolysin to kill all of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

1982
1982
1999
1999

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 19 publications
2
21
1
Order By: Relevance
“…Zucker-Franklin (29) and Hirsch et al (15) reported effects on rabbit granulocytes within 1 min of exposure to SLO. Similar data were reported for SLO action on mouse macrophages (11,22). Hirsch et al (15) found that streptolysin S (SLS) caused its effects on rabbit granulocytes in 15 to 30 min.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Zucker-Franklin (29) and Hirsch et al (15) reported effects on rabbit granulocytes within 1 min of exposure to SLO. Similar data were reported for SLO action on mouse macrophages (11,22). Hirsch et al (15) found that streptolysin S (SLS) caused its effects on rabbit granulocytes in 15 to 30 min.…”
Section: Discussionsupporting
confidence: 66%
“…No lag phase was evident. Similar data have been obtained for other bacterial hemolysins (1,10,16,22). The leukocidal effect of staphylococcal gamma-hemolysin on human leukocytes has also been shown to proceed without a lag phase (10).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…pyogenes infections is unknown. Several investigations of bacterial haemolysins have shown that haemolysins can have leucocytic functions, influence phagocytosis or chemotaxis, or have metabolic activity (OFEK et al, 1972; VAN Errs and ANDERSEN, 1974;ANDERSEN and DUNCAN, 1980). KUME et al (1986) presented data suggesting that the heat-stable haemolysin of Haemophilus pleuropneumoniae affects cell viability and phagocytic ability of porcine pulmonary macrophages in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be speculated that both SLS and SLO, which diffuse away from the proliferating streptococci, might intercept migrating neutrophils to injure their lysosomes, causing massive exocytosis even before the neutro-phi1 has a chance to intercept, phagocytize, and kill the bacteria. Indeed, both SLS and SLO were found to strongly inhibit phagocytosis by human neutrophils (59). These "long-range missiles" can, therefore, eliminate the phagocyte's bactericidal armaments.…”
Section: Sls Acts In Synergic With Oxidants and With Proteinases To Imentioning
confidence: 99%